2023
DOI: 10.3390/separations10060362
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy and HPLC Analysis of Polyphenolic Compounds in a Whole-Plant Extract of Eryngium campestre

Abstract: Due to the constant increase in the number of plant diseases and the lack of available treatments, there has been a growing interest in plant extracts over the past few decades. Numerous studies suggest that plant extract molecules possess valuable antimicrobial activities, particularly against fungi and bacteria. This suggests that these biomaterials could potentially serve as attractive therapeutic options for the treatment of phytopathogen infections. In the present study, we investigated and analyzed the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The anti- Acanthamoeba effect of different compounds of the roots and leaves of the E. planum was investigated by Derda et al ( 2013 ); the results showed that the flavonoid saponin compound isolated from the leaves of E. planum was the most effective at a concentration of 5 mg/ml and has inhibited 76% of trophozoites of Acanthamoeba castellani after 72 h (Derda et al 2013 ). In the study by Al-Askar et al ( 2023 ), the minimum fungicidal concentration (MFC) value of the E. planum on the Fusarium solani fungus in 48 h was 0.5 µg/ml while it was 1 µg/ml for Ketomonarol (Al-Askar et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anti- Acanthamoeba effect of different compounds of the roots and leaves of the E. planum was investigated by Derda et al ( 2013 ); the results showed that the flavonoid saponin compound isolated from the leaves of E. planum was the most effective at a concentration of 5 mg/ml and has inhibited 76% of trophozoites of Acanthamoeba castellani after 72 h (Derda et al 2013 ). In the study by Al-Askar et al ( 2023 ), the minimum fungicidal concentration (MFC) value of the E. planum on the Fusarium solani fungus in 48 h was 0.5 µg/ml while it was 1 µg/ml for Ketomonarol (Al-Askar et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HAL extract was stored in a cool, dry place in a dark-colored glass container to prevent light from breaking down the active compounds 26 . The yield of the extract was calculated as: Yield extract = [HAL dry extract after solvent removal (g)/dry HAL powdered material used in extraction (g)] × 100 27 .…”
Section: Methodsmentioning
confidence: 99%